Identification of novel autoantigens as potential biomarkers in juvenile idiopathic arthritis associated uveitis - Arve-Butler, Sabine; Mossberg, Anki; Kahn, Fredrik; Najibi, Seyed Morteza; Berthold, Elisabet; Król, Petra; Månsson, Bengt; Kahn, Robin (Frontiers in Pediatrics, 2023)
Background: Many children with juvenile idiopathic arthritis (JIA) have autoantibodies, targeting nuclear components (anti-nuclear antibodies, ANA). ANA in JIA is associated with uveitis, an eye inflammation which may cause permanent vision impairment if not detected and treated. However, ANA-testing is neither specific nor sensitive enough to be a clinically reliable predictor of uveitis risk, and the precise autoantigens targeted by ANA in JIA are largely unknown. If identified, specific autoantibodies highly associated with uveitis could be used as biomarkers to facilitate identification of JIA patients at risk. Methods: Antibodies from six ANA-positive, oligoarticular JIA patients, with and without uveitis, were explored by two large-scale methods: (1) screening against 42 100 peptides on an autoimmunity profiling planar array, and (2) immunoprecipitations from cell lysates with antigen identification by mass spectrometry. Tre hundred thirty-five peptide antigens, selected from proteins identified in the large-scale methods and the scientific literature were investigated using a bead-based array in a cohort of 56 patients with oligoarticular- or RF-negative polyarticular JIA, eight of which were having current or previous uveitis. Results: In the planar array, reactivity was detected against 332 peptide antigens. The immunoprecipitations identified reactivity towards 131 proteins. Only two proteins were identified by both methods. In the bead-based array of selected peptide antigens, patients with uveitis had a generally higher autoreactivity, seen as higher median fluorescence intensity (MFI) across all antigens, compared to patients without uveitis. Reactivity towards 17 specific antigens was significantly higher in patients with uveitis compared to patients without uveitis. Hierarchical clustering revealed that patients with uveitis clustered together. Conclusion: This study investigated autoantigens in JIA and uveitis, by combining two exploratory methods and confirmation in a targeted array. JIA patients with current or a history of uveitis had significantly higher reactivity towards 17 autoantigens and a generally higher autoreactivity compared to JIA patients without uveitis. Hierarchical clustering suggests that a combination of certain autoantibodies, rather than reactivity towards one specific antigen, is associated with uveitis. Our analysis of autoantibodies associated with uveitis in JIA could be a starting point for identification of prognostic biomarkers useful in JIA clinical care.